The Impact of Exchange Rate on FDI and the Interdependence of FDI over Time - Joseph D. Alba; Donghyun Park; Peiming Wang (Asian Development Bank (ADB), 2009)
The paper examines the impact of exchange rates on foreign direct investment (FDI) inflows into the United States in the context of a model that allows for the interdependence of FDI over time. Interdependence is modeled as a two-state Markov process where the two states can be interpreted as either a favorable or an unfavorable environment for FDI in an industry. Unbalanced industry-level panel data from the US wholesale trade sector are used in the analysis and yield two main results. First, the paper finds evidence that FDI is interdependent over time. Second, under a favorable FDI environment, the exchange rate has a positive and significant effect on the average rate of FDI inflows.
hdl:11540/1815
Keywords: O31; O47; 330; Basic research; technology creation; technology adoption; economic growth; Wechselkurs; US-Dollar; Auslandsinvestition; Ausländisch; Schätzung; USA